American Women in a World at War: Contemporary Accounts from World War II - Barrett Litoff, Judy; Smith, David C. (Rowman & Littlefield Publishers, 1996)
This title brings together twenty-five writings by women who share their rich and varied World War II experiences, from serving in the military to working on the home front to preparing for the postwar world. By providing evidence of their active and resourceful roles in the war effort as workers, wives, and mothers, these women offer eloquent testimony that World War II was indeed everybody's war. Litoff and Smith combine pieces by well-known writers, such as Margaret Culkin Banning and Nancy Wilson Ross, with important-but largely forgotten-personal accounts by ordinary women living in extraordinary times. This volume is divided into the six sections listed below: Preparing for War In the Military At 'Far-Flung' Fronts On the Home Front War Jobs Preparing for the Postwar World